2005
DOI: 10.1016/j.tcs.2005.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Equitable colorings of bounded treewidth graphs

Abstract: A proper coloring of a graph G is equitable if the sizes of any two color classes differ by at most one. A proper coloring is -bounded, when each color class has size at most . We consider the problems to determine for a given graph G (and a given integer ) whether G has an equitable ( -bounded) k-coloring. We prove that both problems can be solved in polynomial time on graphs of bounded treewidth, and show that a precolored version remains NP-complete on trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…We give a proof that the running time n O(t) of algorithms from [4,20] for different variants of Graph Coloring is essentially the best we can hope for up to a widely believed assumption FPT = W [1]. In particular, we show that…”
Section: Our Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We give a proof that the running time n O(t) of algorithms from [4,20] for different variants of Graph Coloring is essentially the best we can hope for up to a widely believed assumption FPT = W [1]. In particular, we show that…”
Section: Our Resultsmentioning
confidence: 92%
“…The treewidth of G is bounded by k as the graph obtained after removing the vertices The Equitable Coloring problem is a classical problem with a long history starting from 1960s [19,25]. Bodlaender and Fomin have shown that determining whether a graph of treewidth at most t admits an equitable coloring, can be solved in time O(n O(t) ) [4].…”
Section: List Coloring and Precoloring Extension Are W [1]-hard Parammentioning
confidence: 99%
See 1 more Smart Citation
“…For trees, both problems, equitable and b-bounded kcoloring, are studied in [1,5,6,7,14]; a linear-time algorithm that solves the b-bounded k-coloring problem is designed in the first reference. In [3] it is shown that the equitable k-coloring problem is polynomial-time solvable in bounded tree-width graphs but that the precolored version becomes N P -complete, even in trees.…”
Section: Introductionmentioning
confidence: 99%
“…N P-hard in the general case, the complexity of the mutual exclusion scheduling problem has been investigated for several classes of graphs, in particular some classes of perfect graphs (Baker and Coffman 1996;Bodlaender and Fomin 2004;Bodlaender and Jansen 1995;Cohen and Tarsi 1991;Dahlhaus and Karpinski 1998;De Werra 1997;Finke et al 2004;Hansen et al 1993;Jansen 2003;Jarvis and Zhou 2001;Lonc 1991). Unfortunately, few positive results have been published on the subject: for the majority of the classes studied, the problem is shown to be N P-hard.…”
Section: Introductionmentioning
confidence: 99%